USE OF MODERN TECHNICAL LEARNING DEVICES BY STUDENTS DURING THE EDUCATIONAL PROCESS - Andriyanova, O.Yu; Kaskova, L.F.; Amosova, L.I.; Yatsenko, P.I.; Morgun, N.A.; Vashchenko, I.Yu; Artem'ev, A.V. (Ukraïnsʹkij stomatologìčnij alʹmanah (Online), 2024)
The article presents data from a survey of applicants for education and describes the variability of the use of gadgets in the educational process at different stages of learning. The material of the article is based on information received from students, personal teaching experience and the opinion of colleagues. The purpose of this study is to analyze and evaluate the role of modern technical devices and the use of information and computer technologies in practical classes. Studying in higher education is now almost impossible without gadgets. The role and place of the latest technologies, mobile communications, and the Internet makes it possible to use laptops, tablets, smartphones, and other gadgets in pedagogy as efficiently as possible due to their informative and interactive nature and ease of use. A survey was conducted among 115 students of the 4th-5th year of the dental faculty to determine their attitude to the use of gadgets in education. The questionnaire consisted of questions about students' personal attitudes toward the use of gadgets and their role in the educational process. It was found that absolutely all students (100% of respondents) use gadgets and the Internet. Among the sources used to master the discipline, only 4.54% of respondents use paper textbooks, and most students (85.21%) use electronic media (e-textbooks, presentations, manuals, and other files on the subject being studied). The use of ICT in the classroom significantly increases their effectiveness, speeds up the training process, allows the teacher to fully express their creativity, provides visualization, and involves a large amount of didactic material.